Pirólise de resíduos cervejeiros para a produção de adsorventes - Machado, Lauren Marcilene Maciel (2020)
Contamination of water by organic compounds can cause damage to the environment and to humans. Adsorption is a promising process for removing these pollutants. In addition, the adsorbents used can be regenerated. Agricultural residues are a great alternative as routes for the production of adsorbents, as is the case with barley malt bagasse, residue generated during beer production. The residues present both in the farming and in the industrial areas present a high volume of disposal and low application. Thermo-chemical conversion by pyrolysis is one of the alternatives used for the recovery of this residue. In search of alternative solutions the objective of this work was to evaluate the potential of a by-product of the brewing industry through the pyrolysis reaction, and to apply the solid fraction obtained in the removal of effluents containing emerging contaminants. The treatment of these contaminants, such as chlorophenols, through the adsorption process is more effective when using biochars produced by alternative routes (use of waste at no cost and with great availability), such as malt bagasse. The malt bagasse was initially pyrolyzed under different experimental conditions of temperature and isotherm time. For this, a 2k factorial design was used. The experimental optimum condition considering the higher yield of biochar, associated with a greater specific surface area was activated and later the biochars were used for adsorption. The optimal pyrolysis conditions resulted in a temperature of 500 ºC and an isotherm time of 10 min. In this condition, the yields of biochar and pyrolytic oil were 29.7 and 33.89 % m m–1, respectively. The biochar had a mesoporous character with a specific surface area of 6.5 m2 g–1 and the pyrolytic oil obtained is composed mainly of aromatic oxygenated compounds, with palmitic acid being the product with the largest share (27.3%). After the investigation phase of the pyrolysis reaction, biochar activations, characterized as mesoporous, physical activation with (CO2) and chemistry (ZnCl2), revealed surface areas of 161 m² g–1 and 545 m² g–1, respectively. For both activated biochars, the adsorption of 2-chlorophenol was favored under acidic conditions, with the highest adsorption capacity obtained for the biochar activated with ZnCl2. The kinetics and isotherms were represented by the pseudo-second order and Freundlich models, respectively. The maximum adsorption capacity of the ZnCl2 activated biochar was 150 mg g–1. The process was spontaneous and endothermic. The regeneration of the biochar with ZnCl2 was 52.7 mg g–1, for 5 cycles. The ZnCl2 activated biochar exhibited 98% efficiency in the treatment of industrial effluents containing 2-chlorophenol. In summary, this work demonstrated that an available and problematic residue, the malt bagasse, can be simultaneously converted into a mesoporous biochar, into a pyrolytic oil rich in palmitic acid and also into an activated biochar with high potential for the treatment of effluents containing 2-chlorophenol.